Rib desmoplastic fibroblastoma: Video-assisted resection - Buero, Agustín (J Minim Access Surg, 2018)
A 46-year-old man was referred to our department due to chronic chest pain. A computed tomography showed an exophytic image arising from 5th rib that was projected on the middle lobule. The patient underwent an exploratory videothoracoscopic because we couldn't discard lung compromise. A corneal-like lesion emerging from the inner side of the 5th rib was revealed. Complete video-assited resection was done. Histopathology examination revealed a desmoplastic fibroblastoma. To our knowledge this is the first case of desmoplastic fibroblastoma arising from a rib and the second case published in all literature of chest wall involvement.